Keterhubungan Kepercayaan pada Streamer dan Kepercayaan pada Produk dan Pengaruhnya pada Niat Beli dan Kesediaan Membayar Lebih Pengguna Live Commerce - Slamet, Slamet; Indrawati, Iin Dyah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Live commerce media facilitates more transparent trade. This research investigated how trust in a streamer affects trust in a product, as well as the influence on the trust factor on purchase intention and the willingness to pay more. This research fills two empirical gaps. First, the number of studies on live commerce user behavior is still limited. Second, previous research on live commerce is restricted to a single platform and a single product category. SEM-PLS is used for analysis on 956 live commerce user data. Trust in streamer is statistically supported to have a positive effect on trust in product. Streamer trust and product trust are statistically supported to have a positive impact on purchase intention and readiness to pay more. This research is anticipated to add to the academic literature and contribute to generalizing tests on all live commerce platforms and all product categories.